A study to estimate the frequency of Hanifin and Rajka's minor criteria in children for diagnosis of atopic dermatitis in a tertiary care center in South India - Navya Parthasarathy; Aparna Palit; Arun C Inamadar; Keshavmurthy A Adya (Wolters Kluwer Medknow Publications, 2020)
Background: Atopic dermatitis (AD) is a chronic, relapsing inflammatory skin disease characterized by intense pruritus. Hanifin and Rajka's criteria is the most common diagnostic criteria used in the hospital setup, which consists of 4 major and 23 minor criteria. The frequency of minor criteria may vary population wise. Aims: The aim of the study is to estimate the frequency of minor diagnostic criteria of Hanifin and Rajka in children with AD. Methodology: A hospital-based cross-sectional study of 174 children (≤16 years) with AD, was conducted based on history, clinical, and ophthalmological examination. Blood test to assess serum immunoglobulin E (IgE) level was conducted. Results: The most common minor criteria observed were Dennie-Morgan infraorbital fold (71.8%), early age of onset (67.8%), palmar hyperlinearity (67.8%), xerosis (67.2%), pityriasis alba (57.5%), and perifollicular accentuation (47.7%). Out of 143 cases whose serum was tested for IgE level, elevation was seen in 92. History of winter exacerbation was seen in 8% of the cases, while summer exacerbation was seen in none. On the ophthalmological examination of 111 cases, "high reading with no obvious keratoconus" was present in two cases while three cases were labeled as "keratoconus suspect." Conclusion: Clinical features of AD vary with geographical location. The prevalence and severity of AD are influenced by several factors such as ethnic/racial, environmental, and dietary factors. Therefore, it is relevant for dermatologists to have a knowledge regarding common clinical features of AD in a given population for the diagnosis and thereby provide treatment to reduce the morbidity along with appropriate counseling.